Solve for w -2(w+1)+5w=3(w+1)-2

Math
-2(w+1)+5w=3(w+1)-2
Simplify -2(w+1)+5w.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-2w-2⋅1+5w=3(w+1)-2
Multiply -2 by 1.
-2w-2+5w=3(w+1)-2
-2w-2+5w=3(w+1)-2
Add -2w and 5w.
3w-2=3(w+1)-2
3w-2=3(w+1)-2
Simplify 3(w+1)-2.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3w-2=3w+3⋅1-2
Multiply 3 by 1.
3w-2=3w+3-2
3w-2=3w+3-2
Subtract 2 from 3.
3w-2=3w+1
3w-2=3w+1
Move all terms containing w to the left side of the equation.
Tap for more steps…
Subtract 3w from both sides of the equation.
3w-2-3w=1
Combine the opposite terms in 3w-2-3w.
Tap for more steps…
Subtract 3w from 3w.
0-2=1
Subtract 2 from 0.
-2=1
-2=1
-2=1
Since -2≠1, there are no solutions.
No solution
Solve for w -2(w+1)+5w=3(w+1)-2

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top